2019
DOI: 10.7717/peerj.6982
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic identification of membrane-associated placental protein 4 (MP4) as perlecan and characterization of its placental expression in normal and pathologic pregnancies

Abstract: Background More than 50 human placental proteins were isolated and physico-chemically characterized in the 70–80s by Hans Bohn and co-workers. Many of these proteins turned to have important role in placental functions and diagnostic significance in pregnancy complications. Among these proteins was membrane-associated placental protein 4 (MP4), for which identity or function has not been identified yet. Our aim was to analyze the sequence and placental expression of this protein in normal and complicated pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 86 publications
0
4
1
Order By: Relevance
“…It is a protective molecule whose level increases as a response to the abnormal autophagic reaction that contributes to the pathogenesis of PE. 26 Contrary to our study findings, a study by Chui et al, 2012 27 found that protein expression of Perlecan and its mRNA were significantly reduced in PE cases, they explained these findings by saying that Perlecan has an angiogenesis-inducing effect and a decrease in its serum level contributes to the pathogenesis of PE by reducing trophoblast invasion. The small sample size of our groups could explain these unexpected and divergent results…”
Section: Discussioncontrasting
confidence: 99%
“…It is a protective molecule whose level increases as a response to the abnormal autophagic reaction that contributes to the pathogenesis of PE. 26 Contrary to our study findings, a study by Chui et al, 2012 27 found that protein expression of Perlecan and its mRNA were significantly reduced in PE cases, they explained these findings by saying that Perlecan has an angiogenesis-inducing effect and a decrease in its serum level contributes to the pathogenesis of PE by reducing trophoblast invasion. The small sample size of our groups could explain these unexpected and divergent results…”
Section: Discussioncontrasting
confidence: 99%
“…At the protein level, the expression of five proteoglycans (decorin, glypican-1, glypican-3, perlecan, syndecan-2) of the nine measured was significantly decreased in the placentas of women with pre-eclampsia compared to gestational-age-matched controls [ 20 ]. Regarding perlecan protein levels in the placenta, our study found the same direction of change in late-onset pre-eclampsia, which constitute the majority of cases, while an opposite directional change was observed in early-onset pre-eclampsia [ 78 ]. This may reflect the distinct placental pathologies of these clinically different pre-eclampsia subtypes.…”
Section: Resultsmentioning
confidence: 84%
“…Immunostained TMA images were semi-quantitatively scored by two examiners blinded to the clinical information with an immunoreactive score modified from one previously used in our studies [18,65,74,100,101,102]. Trophoblastic immunostaining intensity was graded as 0 = negative, 1 = weak, 2 = intermediate, and 3 = strong.…”
Section: Methodsmentioning
confidence: 99%